Critical review of the effects and role of the Climate Change Response Act of 2023 in Taiwan’s net-zero ambition of 2050 - Anton Ming-Zhi Gao; Chien-Te Fan; Tsung Kuang Yeh; Chao-Ning Liao (Carbon Management)
In 2022, the Taiwanese government is set to develop Taiwan’s Pathway to Net-Zero Emissions by 2050 by identifying 12 strategies, including wind/photovoltaic power, hydrogen energy, innovative energy, power systems and energy storage, and energy saving and efficiency. Formulating 12 action plans and revising the 2015 Greenhouse Gas Management and Reduction Act were the two key pillars of the legal strategy. The new Climate Change Response Act (CCRA) was adopted in January 2023, and 12 action plans were adopted in April 2023. This study evaluates how the key pillars of legal strategy can contribute to achieving such an ambitious net-zero target. We divided the legal measures of the 2015 and 2023 acts on carbon pricing, regulatory tools, institutional reform, and other emission reduction measures; compared the changes before and after the CCRA; and evaluated their impacts on further emission reductions. We found that the CCRA might play a minor role in improving emission reduction initiatives despite continuing promotion from government claims. Buying ‘indulgences’, that is, global offsets, could be the only way for Taiwan to meet its goal of net-zero by 2050.